TOOLS FOR MAKING EFFECTIVE MANAGEMENT DECISIONS - HRYHORIEV, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is a comprehensive analysis of modern tools for making effective management decisions at enterprises, in particular in conditions of threats, risks and challenges related to technologies, geopolitical instability and organizational complexity. It is proved that the effectiveness of management decisions determines not only the success of an individual enterprise, but also its ability to adapt, survive and develop. It is substantiated that management activity in modern conditions is characterized by a high level of complexity, dynamic of the environment and the need for strategic consistency. It is shown that the functioning of an effective management system is a critical factor in ensuring the sustainable development of the enterprise, since it allows you to respond promptly to changes in the environment, optimize the use of resources and maintain competitiveness in the market. The problems that influence management decisions, namely information asymmetry, cognitive restrictions on managers, organizational fragmentation, uncertainty of the environment, imperfection of the methodological apparatus and socio-psychological aspects, are systematized and characterized. The basic tools in making management decisions that are able to compensate for identified restrictions and provide systematic support of management activities are summarized. A scheme of management decision making using modern tools according to the directions of transformation of business processes is formed. It is substantiated that modern tools, such as decision support systems, Big Data analytics, script modeling, decision tree, SWOT analysis and emotional intelligence tools, provide a comprehensive approach to management, combining a strategic vision with tactical flexibility.
Keywords: Management decision; effective management decision; tools; decision-making system; dynamic environment; adaptation; enterprise